Molecular Identification of Pathogenic Leptospirosis with Zoonotic Potential in Urban Rats (Rattus Rattus) in Banyuwangi District - Maya Nurwartanti Yunita; Bodhi Agustono; Muhammad Thohawi Elziyad Purnama (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
Leptospirosis is a zoonotic disease that occurs globally. Leptospires are transmitted through the urine of infected mice, through injured skin or mucosal invasion. Infection can occur through direct contact or through contact with contaminated water or soil. This qualitative research uses a combination of epidemiological studies with a case study approach. Rat urine metabolism samples will be tested by testing the base pair chain through the Polymerase Chain Reaction method for leptospirosis. Electrophoresis results showed 5% percent of positive samples with 330 bp. The conclusion of this study, the molecular identification of leptospirosis from rat urine using the Polymerase Chain Reaction technique are found positive results so prevention is needed to control the distribution of pathogenic leptospirosis bacteria. Urban rats (Rattus rattus) in leptospirosis transmission are considered as the most important leptospira reservoir, because high population densities of this species can cause an increase in the spread of leptospirosis. Keywords: Banyuwangi, Leptospirosis, Urban rats, Zoonosis